Thermodynamic Deprotonation of N,N'-Disubstituted Violuric Acid and Thiovioluric Acid in Dioxane-Water Mixtures - Sorabh Singh, Deep; Singh, B.R. (Asian Journal of Chemistry, 2010)
Thermodynamic deprotonation constants (pKaT) of diphenyl violuric acid [DPVA], di-p-tolylvioluric acid [D-p-TVA], di-m-tolyl violuric acid [D-m-TVA], di-o-tolyl violuric acid [D-o-TVA], di-p-xylyl violuric acid [D-p-XVA], di-m-xylyl violuric acid [D-m-XVA], di-o-xylyl violuric acid [D-o-XVA], Di-α-napthyl thiovioluric acid [D-α-NTVA] and di-β-napthyl thiovioluric acid [D-β-NTVA] have been determined in different mole fraction of dioxane [0.174- 0.350] at 20, 30 and 40 ± 0.10 ºC. The thermodynamic deprotonation constant (pKaT) values do not vary linearly with the reciprocal of the dielectric constant of medium, but a plot of pKaT versus the mole fraction of dioxane is linear at all the given temperatures. The mean ionic radii r± for violurates and thioviolurate ions, being in the region of 2.15-2.75 Å, slightly increases with dioxane percentages. The values of ΔGo, ΔHo and ΔSo have been evaluated. The effect of temperature, as well as medium effect are briefly discussed.